FORMULASI DAN UJI STABILITAS FISIK TABLET KEMPA EKSTRAK DAUN PEPAYA ( Carica Papaya. L) - Beta Herilla Sekti; Agung Permata; Neysa Oktadiva S. P (HERBAPHARMA : Journal of Herb Farmacological, 2022)
Papaya leaf (Carica Papaya L.) is a plant that contains alkaloids, flavonoids, tripertinoids, saponins and tannins that are useful for treating diabetes. This study aims to obtain compressed tablets of papaya leaf extract and determine the effect of the concentration of PVP K30 as a binder on the physical properties of compressed tablets. The study used an experimental method, with a comparison of formula 1 = 1%, formula 2 = 3% and formula 3 = 5% and tested the physical properties of tablets. The results showed that the tablets met the requirements and only one formula did not meet the tablet friability test. The conclusion of the research on compressed tablets of papaya leaf extract with different concentrations of PVP K30 as a binder met the requirements for the physical test of tablets